Working Mothers: Their Problems and Coping Strategies - An Exploratory Study / Sources of Stress and Coping Mechanisms among Filipinas in West Germany and Holland / Filipino-Japanese Couples: Communication Variables and Marital Satisfaction - Sycip, L.; Samonte, E.; Samonte, E. (Review of Women's Studies; Vol 1 No 2 (1991): Review of Women's Studies Volume I, Number 2 (1990-1991))
---